2022
DOI: 10.1037/xge0001152
|View full text |Cite
|
Sign up to set email alerts
|

The language of accurate and inaccurate eyewitnesses.

Abstract: We thank David Dobolyi, Gurpreet Reen, and Melissa Colloff for their thoughts on an earlier version of this manuscript. We also thank Ian Dobbins and Justin Kantner for their helpful scripts. Lastly, we thank Caroline Levenson, Kelis Johnson, Emma Balsam, and Annie Han for their valuable assistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Importantly, ChatGPT may categorize phrases differently when presented with (a) the same phrase set, and (b) the same prompts because of its probabilistic algorithm. Consistent interpretation is difficult, likely because of the unique information provided in own words confidence statements (Seale‐Carlisle et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, ChatGPT may categorize phrases differently when presented with (a) the same phrase set, and (b) the same prompts because of its probabilistic algorithm. Consistent interpretation is difficult, likely because of the unique information provided in own words confidence statements (Seale‐Carlisle et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Encouragingly, verbal and numeric confidence have been shown to be similarly predictive of identification accuracy (e.g., Mansour, 2020). Verbal confidence statements provide unique diagnostic information (Seale‐Carlisle et al, 2022; Steblay & Wells, 2023), but oftentimes, the language used is vague and subject to misinterpretation (Budescu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Another developing line of research is provided by Searle-Carlisle and colleagues (e.g., Searle-Carlisle et al, 2019, 2022), who have applied machine-learning techniques in the lab to examine witness’s verbal confidence statements. They conclude that verbal confidence statements provide unique diagnostic information about identification accuracy, and they encourage future work regarding the predictive properties of specific words.…”
Section: Discussionmentioning
confidence: 99%
“…Recent computerized approaches represent a novel way of understanding the meaning of verbal confidence statements. Seale‐Carlisle et al (2021) used machine‐learning techniques to analyze the content of verbal confidence statements for cues to accuracy. This approach revealed that verbal confidence was predictive of accuracy and that the content of verbal confidence statements contained additional diagnostic cues beyond information provided by numeric confidence.…”
Section: Introductionmentioning
confidence: 99%